If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + -4) + 8x + -4 = 0 Reorder the terms: -3(-4 + 2x) + 8x + -4 = 0 (-4 * -3 + 2x * -3) + 8x + -4 = 0 (12 + -6x) + 8x + -4 = 0 Reorder the terms: 12 + -4 + -6x + 8x = 0 Combine like terms: 12 + -4 = 8 8 + -6x + 8x = 0 Combine like terms: -6x + 8x = 2x 8 + 2x = 0 Solving 8 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 0 + -8 2x = 0 + -8 Combine like terms: 0 + -8 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 4a^2-21a+5= | | (3*6/2)v+10=9v+9 | | 12x-10=-6x+14 | | 2m=-18-5 | | 2m=-12-5 | | -5x-18=-268 | | -2(8x+5)=-10(1-3x) | | 8y+2x=-4 | | 2m=-6-5 | | 3x+3x=2x-4 | | -3(-3y+2)-(4y-3)-3y+5= | | 162x^3+750=0 | | 4(x-3)+7=19 | | 2+6x=38 | | x-(-21)=71 | | 4=7p-5p | | z=xy-xy^2 | | 2(g-2)-4=2(g+3) | | (1+7)-(5+3)= | | 3a+a+2-2a-1=3a+6 | | 4m+11m-7=8 | | x-18=-18 | | 6x-2(x+4)=8(x-2)+6 | | 2y-5=40 | | 60x^3-24x-3x=0 | | m-6=7 | | (7x+4)(2x-5x-3)=0 | | 69+1x=69+1x | | 2y-5= | | 4+6b=8(4b-6) | | 69+1=69+1x | | 1.5x-7=0.5 |